Understanding Patient Flow from the Perspectives of Patient Movement Experts - Pieter Van Dam; Mitchell Dwyer; Malgorzata O'Reilly; Sarah Prior; James Montgomery; Richard Turner (ACHSM, 2024)
Background: Poor patient flow or patient movement through a healthcare organisation can lead to adverse outcomes for patients and organisational inefficiency. Many hospitals have addressed suboptimal patient flow by increasing resources, such as bed stock and staffing; however, this is an unsustainable approach. In determining the nature of poor patient flow issues, it is important to collect data from healthcare professionals who manage patient flow daily. Doing so provides insights into the current state of patient flow management in its entirety, whilst also helping with the development of sustainable solutions. Methods: Thirteen semi-structured interviews were conducted with healthcare professionals who were directly involved with patient flow at a referring hospital in Tasmania, Australia. Results: Using a thematic analysis method, four major themes were developed. The first major theme was: 'managing patient flow' which centered around known and unknown demands on bed availability. The second theme, 'communication for decisions', highlighted the essential role of communication in maintaining patient flow. The third theme, 'tools as enablers and barriers, relates to the number of software programs which can both help and hinder patient flow. The final theme of 'increasing complexity' is related to an apparent trend towards greater numbers of patients requiring care of an increasingly specialised nature. Conclusions: The findings of this study provide great insights into patient flow issues, with potential solutions identified to address them.